Burden of Childhood Cancer in Nepal: An Analysis of GLOBOCAN Data 2022 - Shrestha, Gambhir; Shakya, Sujata; Aryal, Surabhi; Yadav, Alisha; Paudel, Bishal (Asian Pacific Journal of Cancer Care, 2026)
Introduction: Childhood cancer poses a significant public health challenge in low-middle-income countries, such as Nepal. This study reports the burden of childhood cancer in Nepal. Materials and Methods: This study utilized the data from the latest GLOBOCAN 2022 database to present estimates of childhood cancer in Nepal. The data were described as incidence, prevalence, and mortality stratified by age, gender, and cancer type. The projected trend of childhood cancer was also analyzed until the year 2050. Results: In 2022, there were an estimated 936 childhood cancer cases in Nepal, including 330 new cases with an age-standardized rate (ASR) of 4.1 per 100,000 and 121 deaths with an ASR of 1.5 per 100,000. The most common cancers were leukemia, non-Hodgkin lymphoma, and brain and central nervous system. The projected trend in 2050 indicated a decrease in childhood cancer cases and mortality by 10.6% and 10.7%, respectively. Conclusion: This study highlighted the burden of childhood cancer in Nepal, aligning with global and Asian trends. Urgent action is required, emphasizing a comprehensive approach that includes raising awareness, early diagnosis, treatment, resource allocation, and policy integration to effectively alleviate the burden of childhood cancer.